2021
DOI: 10.1002/jmv.27281
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic characteristics of cases with reinfection, recurrence, and hospital readmission due to COVID‐19: A systematic review and meta‐analysis

Abstract: Recent studies reported that some recovered COVID‐19 patients have tested positive for virus nucleic acid again. A systematic search was performed in Web of Science, PubMed, Scopus, and Google Scholar up to March 6, 2021. The pooled estimation of reinfection, recurrence, and hospital readmission among recovered COVID‐19 patients was 3, 133, and 75 per 1000 patients, respectively. The overall estimation of reinfection among males compared to females was greater. The prevalence of recurrence in females compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
5
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(106 citation statements)
references
References 65 publications
3
80
5
2
Order By: Relevance
“…Published data on the prevalence of SARS-CoV-2 reinfection highlighted their low rates, ranging from 0.1% to 0.65% [ 5 , 16–18 ]. In our study, we found that overall, 0.38% of patients with SARS-CoV-2 infection diagnosed at our institute had sustained a prior infection with this virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Published data on the prevalence of SARS-CoV-2 reinfection highlighted their low rates, ranging from 0.1% to 0.65% [ 5 , 16–18 ]. In our study, we found that overall, 0.38% of patients with SARS-CoV-2 infection diagnosed at our institute had sustained a prior infection with this virus.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted among 829 patients recovered from COVID-19, 87 had no detectable IgG against SARS-CoV-2, of whom 25 (28.7%) were reinfected 1–3 months after their first infection, while there was just one case of reinfection 4.5 months after initial recovery among those with detectable IgG (0.1%) [ 4 ]. Recently, a meta-analysis showed that the pooled estimation of reinfection among recovered patients was 0.3%, with a high heterogeneity among studies, and it was more common among male patients [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mass-vaccination against COVID-19 is effective and protects against severe COVID-19 in real-world settings (34,35). Decreases of antibody levels and increases of breakthrough infections point to waning immunity of vaccination over time (36)(37)(38)(39). However, despite the decline in antibody levels, protection from severe disease and hospitalization remains high (40,41), suggesting that persisting cellular immunity drives the immune response and prevents viral dissemination when antibodies disappear.…”
Section: Introductionmentioning
confidence: 99%
“…Several works have been carried out to improve the performance of these predictive models using evaluation metrics [ 130 , 131 ]. Similarly, many studies have been conducted regarding the COVID-19 case readmission rates and factors [ 132 , 133 ].…”
Section: Related Reviews In the Fieldmentioning
confidence: 99%